Classification of shoulder diseases in older adult patients: a narrative review - Hyo-Jin Lee; Jong-Ho Kim (The Ewha Medical Journal)
This review classifies and summarizes the major shoulder diseases affecting older adults, focusing on rotator cuff disease, frozen shoulder, osteoarthritis, and shoulder instability. It explores each condition's pathophysiology, risk factors, clinical presentation, diagnostic approaches, and treatment strategies to guide clinicians in optimizing patient outcomes and enhancing quality of life. Age-related degenerative changes, comorbidities, and distinct etiological factors contribute to the presentation of shoulder disorders in older adults. Rotator cuff disease ranges from tendinopathy to full-thickness tears and is influenced by genetic predispositions, inflammatory cytokines, and muscle quality. Frozen shoulder results from fibroproliferative changes in the capsule, leading to significant pain and restricted motion. Osteoarthritis involves cartilage degeneration and bony remodeling, often necessitating surgical interventions such as arthroplasty. Shoulder instability, though less frequent, is complicated by associated injuries like rotator cuff tears and fractures, requiring tailored management strategies. Advances in imaging techniques, biologic treatments, and surgical procedures, particularly arthroscopic and arthroplasty options, have improved diagnostic accuracy and therapeutic outcomes. A thorough classification of shoulder diseases in older adult patients highlights the complexity of managing these conditions. Effective treatment requires individualized approaches that integrate conservative measures with emerging biologic or surgical therapies. Future research should focus on targeted interventions, standardized diagnostic criteria, and multidisciplinary collaboration to minimize disability, optimize function, and improve overall quality of life in this growing patient population. Multimodal strategies, including patient education, structured rehabilitation, and psychosocial support, further enhance long-term adherence and outcomes. Ongoing vigilance for comorbidities, such as osteoporosis or metabolic disorders, is necessary for comprehensive care.